Characteristics of composition, area and status of coral reefs at submerged banks and shoals on the continental shelf of Southern Vietnam - Long, Nguyen Van; Tran , Van Binh; Thai, Minh Quang; Nguyen-Le, Thao My; Malyutina, Marina (Vietnam Journal of Marine Science and Technology, 2025)
The continental shelf off southern Vietnam, from Khanh Hoa to Ba Ria-Vung Tau provinces, contains numerous submerged banks and shoals. These locations are considered to have significant potential, not only for their distinctive landscapes but also for their valuable biodiversity and critical marine resources. This study was based on the compilation and analysis of data from U.S. Navy nautical charts, Vietnamese maps, and previously published reports from before 2001, combined with GIS techniques to build a 3D underwater terrain model and calculate the area of 10 specific submerged banks and shoals on southern Vietnam’s continental shelf. Additionally, coral reef conditions at these sites were assessed alongside biodiversity assessments during May-June 2023. The calculations show that the total area of the 10 submerged banks and shoals was approximately 19,144 hectares. Of these, 9 locations, including Grand Bank, De Thuy Trieu Bank, Phan Rang Bay Shoal, Breda Shoal, Hollandias Bank, De Britto Bank, De L Astrolabe Bank, Bishop Bank, and Catwick Bank, had coral reefs distributed over 17,257 hectares. However, coral reefs were absent in the southeastern shoal group near La Gan Cape. Overall, coral reefs in these regions were severely degraded, with live coral cover ranging from 5–30%, except for Phan Rang Bay Bank, which had slightly higher coverage (31–50%). Macroalgal coverage was notably high, ranging from 5% to 75% per site.